2013
DOI: 10.1016/j.jsv.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Piecewise polynomial chaos expansion with an application to brake squeal of a linear brake system

Abstract: . Piecewise polynomial chaos expansion with an application to brake squeal of a linear brake system. Journal of Sound and Vibration, Elsevier, 2013, 332, pp.577-594. <10.1016/j.jsv.2012 AbstractThis paper proposes numerical developments based on polynomial chaos (PC) expansions to process stochastic eigenvalue problems efficiently. These developments are applied to the problem of linear stability calculations for a simplified brake system: the stability of a finite element model of a brake is investigated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…Adaptive strategies can be implemented to recursively refine the partition based on a given criterion [12,34,35]. Here, the partition will be set a priori and the quality of the global expansion will be measured by .…”
Section: Using a Multi-element Basismentioning
confidence: 99%
“…Adaptive strategies can be implemented to recursively refine the partition based on a given criterion [12,34,35]. Here, the partition will be set a priori and the quality of the global expansion will be measured by .…”
Section: Using a Multi-element Basismentioning
confidence: 99%
“…Recent papers propose evaluation of Hopf bifurcation point (when stability changes) using MEgPC for a system with dry friction when one parameter (the friction coefficient) varies but does not investigate the non-linear effects in the unstable range (see (Nechak et al, 2013) for a 2-dofs system and (Sarrouy et al, 2013) for a finite element model of a brake).…”
Section: Some Recent Work Uses Polynomial Chaos Expansion and Derivatmentioning
confidence: 99%
“…Brake noise is a largely elusive phenomenon, partly due to the stochastic features of friction and the relevant timevarying factors such as interface profile, wear, interface films. The theoretical stochastic models have been developed to address variability and uncertainty in brakes noise [25][26][27][28][29][30][31][32][33][34]. A typical study is reported in [26], which documented a robust design of a disc brake through structural optimization using the complex eigenvalue approach, considering the variation of friction coefficient, major elastic constants and the effect of material worn-off.…”
Section: Historic Perspectives: the Example Of Brake Noisementioning
confidence: 99%
“…In [33], neural network method is used to predict disc brake performance. In [34], polynomial chaos expansions approach is used to tackle with stochastic eigenvalue problems with applications to linear stability calculations for a simplified brake system in which the stability of a finite element model of a brake is investigated when its friction coefficient or the contact stiffness are modeled as random parameters. Results are compared to Monte Carlo simulations.…”
Section: Historic Perspectives: the Example Of Brake Noisementioning
confidence: 99%